Proposta de um minicurso de Astronomia para alunos do Ensino Fundamental II - Pesquero, Lucas Canevarolo (2015)
In this dissertation, an astronomy workshop is proposed which can be used as preparation for Brazilian Olympics of Astronomy, but whose main goal is to become one more tool for studies in such discipline. Even those who did not attend a specific discipline of astronomy throughout his academic life are able to apply this workshop, because, to each class of the sequence, texts and videos with supplementary information was given, making it accessible to all interested teachers. To justify the need for this teaching sequence, this dissertation starts with a national overview of astronomy education and their main weaknesses, then describes the Brazilian Olympics of Astronomy and its achievements, reports previous workshop experiences to, only at the end, propose a possible activities script.